Polarization holographic imaging using speckle pattern illumination - Vinu R.V.; Chen Z.; Pu J.; Otani Y.; Singh R.K. (My University, 2025)
We present a technique for polarization holographic imaging that employs the complex speckle pattern (rather than a uniform field) to illuminate the sample and utilizes the randomness of the speckle pattern for image enhancement. The vectorial wave front is recovered by developing a polarization holographic imaging system with the potential of simultaneous detection of orthogonal polarization components. Basic principle and preliminary results of the technique are discussed. © 2018 OSJ